Alexander v. Sandoval:A Setback for Civil Rights - Welner, Kevin G. (Education Policy Analysis Archives, 2001)
This article confronts the serious implications of a recent U.S. Supreme Court decision, Alexander v. Sandoval, which eliminated an important legal avenue for civil rights plaintiffs. For over 35 years, individuals have been allowed to bring lawsuits directly challenging violations of rights set forth in the federal regulations implementing Title VI of the 1964 Civil Rights Act. Because these actions could be grounded in proof of disparate impact, rather than discriminatory intent, they allowed for some claims that could not go forward under other legal authorities, such as the Fourteenth Amendment. While the author concludes by identifying key remaining options, he highlights the real damage done by this decision.